Economic Aspects of Final Energy Consumption in Ukraine: Prospects of Implementation of the Positive Experience of the European Union - Yakymchuk, Alina; Popadynets, Nazariy; Yakubiv, Valentyna; Maksymiv, Yuliia; Hryhoruk, Iryna; Matiychuk, Lubomyr; Horyslavets, Pavlo (International Journal of Energy Economics and Policy, 2023)
The lack of a proper system for the use of energy resources is a nationwide problem in Ukraine. Payment for the consumed services for energy carriers mainly formed according to “consumption rates”, which can significantly ex-ceed the actually received amount of services and leads to an unjustified in-crease in the cost of energy resources. All this requires a search for new tools to stimulate energy intensity, effective accounting of the total volume of ener-gy consumption and the introduction of the best foreign experience in the field of energy saving in Ukraine. The analysis of energy consumption in the coun-try made it possible to identify the existing problems that subsist in the energy sphere today and provided an opportunity to propose ways to eliminate imbal-ances. The proposed methodology makes it possible to build models for estab-lishing the relationship between energy intensity and final energy consump-tion in Ukraine. Evaluation of foreign European experience makes it possible to implement the most necessary reforms and measures in domestic practice to improve the sphere of energy consumption.